(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Ethylene glycol monomethyl ether is a toxicant with wide industrial applications. This study is aimed at investigating its effect on the antioxidant system of the reproductive organs of male rats. Fifty male Wistar rats were distributed into five groups. Group I received distilled water, Groups II-V received EGME at 100, 200, 300 and 400 mg/kg body weight respectively. All administrations were done orally for fourteen days and the weight was monitored weekly. On day fifteen, the animals were sacrificed and reproductive organs were collected and weighed. The testes and epididymes were processed for the biochemical estimations, histopathology and spermatozoa analysis. The percentage body weight gained weekly and the relative weight of the testes reduced significantly (p < 0.05) in the treatment groups. The spermatozoa analysis showed decreases in the treatment groups. In the testis and epididymis, various antioxidant parameters such as superoxide dismutase and glutathione-S-transferase were affected. The histopathology results confirmed the biochemical findings. The study suggests that EGME exerts deleterious effects on the testes and epididymes by increasing the oxidative load in rats.